Experimental Study on Steel to FRP Bonded Lap Joints in Marine Applications - Çiçek Özes; Nurhan Neşer (Advances in Materials Science and Engineering)
Steel structures coated with fiber-reinforced polymer (FRP) composites have gained wide acceptance in marine industry due to their high strength-to-weight ratio, good protection from environmental degradation, and impact loads. In this study, adhesive bonding performance of single-lap bonded joints composed of steel coated with FRP has been investigated experimentally for three different surface roughness and two epoxy types. Single-lap bonded joints have been tested under tensile loading. The adhesive bonding performance has been evaluated by calculating the strain energy values. The results reveal that the surface roughness of steel has a significant effect on the bonding performance of steel to FRP combinations and the performance of the resin can be improved by using the primer in an economical way.